Double opposite end injection capillary electrophoresis with contactless conductometric detection for simultaneous determination of chloride, sodium and potassium in cystic fibrosis diagnosis - Kubáň, Petr; Greguš, Michal; Pokojová, Eva; Skřičková, Jana; Foret, František (Journal of Chromatography A, 2014)
A novel approach for diagnosis of cystic fibrosis is presented. A simple and fast procedure to obtain sweat sample was developed. It consists of repeatedly wiping the skin of the forearm with deionized water moisturized cotton swab and extraction in 1mL of deionized water. Double opposite end injection capillary electrophoresis with contactless conductometric detection is used for the analysis of the extract. Chloride, sodium and potassium as the three target ions that participate in the ion transfer across the cellular membranes, and are affected by CF, are simultaneously determined in approximately 3min in a background electrolyte containing 20mM 2-(N-morpholino)ethanesulfonic acid, 20mM l-histidine and 2mM 18-crown-6. By using the target ion ratios rather than the concentrations of each individual ion combined with principal component analysis, the diagnosis of CF can be made more accurately and greatly reduce the number of false positive or negative results as is often the case when single ion (chloride) is analyzed.